Implementation on financial assistance policy of political parties in 2015-2018 - SURBAKTI, E.; SULAEMAN, A.; ALAMSYAH D, N.; KARTINI, D.S. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This study departs from the problem of financial assistance policy to political parties in the province of West Java according to the theory of Grindle et al. While the Policy Context consists of the power, interests, and strategies of the actors, compliance, and response of implementers, institutions, and characteristics of the regime that are still not running optimally. The program and policy (content) and policy context are important factors in determining the success or failure of the Implementation of the Use of Financial Aid for DPD PDIP Political Parties and DPD Gerindra Party in West Java Province. RESUMEN Este estudio parte del problema de la política de asistencia financiera a los partidos políticos en la provincia de Java Occidental según la teoría de Grindle et al. Si bien el Contexto de Política consiste en el poder, los intereses y las estrategias de los actores, el cumplimiento y la respuesta de los implementadores, las instituciones y las características del régimen que aún no están funcionando de manera óptima. el programa y la política (contenido) y el contexto de la política son factores importantes para determinar el éxito o el fracaso de la implementación del uso de ayuda financiera para los partidos políticos DPD PDIP y el partido DPD Gerindra en la provincia de Java Occidental.